Implementasi Teknik Modeling untuk Mengembangkan Perilaku Prososial Anak Usia 4-5 Tahun - Nanik Faridah; Ari Purnomo Endah Aflahani (JURNAL LENTERA ANAK, 2021)
Prosocial behavior is social behavior that is helpful, constructive, and positive, which is the opposite of antisocial behavior. Its aim is to master understanding and proficiency in social problems. The phenomenon that occurs in group A, RA Masalikil Huda, has poor prosocial behavior. This was found by students who still did not want to mingle with their friends, did not want to share something they had with their friends and there was no sympathy in the students. So it needs efforts to develop the social skills of students with modeling techniques. The purpose of this study was to determine the social development of students using modeling techniques. The method used in this research is descriptive qualitative. The subjects in this study were students from group A RA Masalikil Huda who were still in the low category of prosocial behavior. Data collection techniques in this study using interviews, observation and documentation. Based on the research results, it can be concluded that the model teacher (researcher) in group A class uses several stages in the modeling process including: attention, giving stimulus, production, motivation and reinforcement. Through these stages, it turns out that it makes it easier for the model or teacher to develop the social for group A's children. Modeling techniques in developing students 'prosocial behavior are said to be effective in order to foster, develop and even improve the quality of students' prosocial behavior.